Role of myocardial viability in functional ischaemic MR - Waleed Atout (The Egyptian Heart Journal, 2014)
Functional ischaemic mitral Regurgitation myocardial viability as a predictor of postoperative outcome after isolated coronary artery bypass grafting. Ischaemic cardiomyopathy is the most common cause of heart failure in the United States. 1This advanced form of coronary artery disease is marked by diffuse myocardial damage, left ventricular remodeling, and often functional ischemic mitral regurgitation (IMR). Patients with Moderate functional ischaemic MR in ischaemic cardiomyopathy will benefit from mitral valve repair at the time of CABG or will benefit from CABG alone without mitral valve repair. Methods: The study population consisted of 135 consecutive patients (age, 65 ± 9 years; 81% male) with ischaemic heart disease and moderate IMR referred electively for isolated CABG who met the following criteria: stable left ventricular (LV) dysfunction with an LV ejection fraction <45% for at least 3 months and stable moderate IMR (vena contracta width, 0.3–0.7 cm; ratio of jet area to left atria [LA] area, 20–40%) on 2 different examinations performed at least 1 month apart during stable conditions. In the presence of qualifying LV dysfunction, an additional 2 criteria were required to diagnose IMR: the presence of apical displacement of mitral leaflets and the absence of organic leaflet lesions. Assessment of myocardial viability was not used for patient selection. All patients included in the study had CABG as the sole procedure. Dyssynchrony between the papillary muscles was determined by tissue Doppler imaging. Myocardial viability was assessed by single-photon emission computed tomography. Results: The absence of preoperative papillary muscle dyssynchrony and presence of viability in myocardial segments adjacent to papillary muscles were associated with improvement in postoperative functional ischaemic MR in >90% of patients. In contrast, the absence of myocardial viability and presence of significant papillary muscle dyssynchrony (e.g. scar in the region of posterior papillary muscle) were associated with no improvement or worsening postoperative IMR. This study shifts the focus from the mitra l valve to myocardial viability and function as the primary determinants of recovery from moderate functional ischaemic MR after isolated CABG. The results of this study will have a strong impact on the 3 key elements in the care of patients with ischaemic cardiomyopaihy and functional ischemic MR: Diagnostic workup, therapeutic approaches, and interpretation of outcomes. Myocardial viability can be determined by dobutamine stress echocardiography, single-photon emission compuled tomography, positron emission tomography, or magnetic resonance imaging. Conclusions: The authors recommend isolated CABG for patients with functional ischemic MR if there is: 1 – Viable myocardium. 2 – And No ventricular dyssynchrony. The absence of viability or presence of ventricular dyssynchrony is indicative of advanced-stage ischaemic cardiomyopathy in which recovery from functional ischemic MR with isolated CABG is unlikely; in these patients, concomitant mitral valve repair should be considered.